The Social Profile of Farmers On Pest Control’s Techniques In Rice Plant at Plosoklaten - Susanti, Ambar; Anshori, Moh; Nasiruddin, Mohamad; Hariri, Rif'an (AGARICUS: Advances Agriculture Science & Farming, 2025)
Jarak Village, located in the Plosoklaten Subdistrict, exhibits considerable promise in the agricultural sector. It has potential to contribute the local economy through the production of food crops, horticulture, and livestock. Of these potential benefits, the food crop sector stands out, particularly in regard to rice production. The purpose of this study was to determine the relationship between age, education level, length of farming business with integrated pest control in rice plants.This research was conducted from October 2024 - January 2025. The analysis of the data was executed through the implementation of the rank Spearman method. The relationship between the age of respondents and pest control techniques on rice plants showed insignificant results in Jarak Village, Plosoklaten District, Kediri. A non-significant relationship was identified between education and pest control techniques in rice plants in Jarak Village, Plosoklaten District, Kediri. A substantial correlation has been identified between the duration of agricultural practices involving pest management techniques in rice plants in Jarak Village, Plosoklaten District, Kediri Regency